2011
DOI: 10.3390/medicina47050040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of the Human ACE and ACTN3 Genes and Their Association With Functional Muscle Properties in Lithuanian Elite Athletes

Abstract: Background and Objective. Based on the results of many studies, the angiotensinconverting enzyme (ACE) and the α-actinin-3 (ACTN3) genes are considered strong candidate genes associated with human physical performance. On the other hand, the data regarding the association of the ACE I/D and ACTN3 R/X polymorphisms with human physical performance in different populations have been conflicting. The objective of our research was to evaluate the significance of these genetic variants on muscle performance phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 15 publications
5
41
0
3
Order By: Relevance
“…In the water polo group, the ID genotype (62.96%) was conclusively higher than the other two genotypes. Similar results were found in a study with Lithuanian athletes (6). With regard to the "mixed athletes" group (both anaerobic and aerobic energy production), the percentage of ID genotype was 47.70%.…”
Section: Discussionsupporting
confidence: 76%
“…In the water polo group, the ID genotype (62.96%) was conclusively higher than the other two genotypes. Similar results were found in a study with Lithuanian athletes (6). With regard to the "mixed athletes" group (both anaerobic and aerobic energy production), the percentage of ID genotype was 47.70%.…”
Section: Discussionsupporting
confidence: 76%
“…However, once we explored this association in a relatively large cohort of team-sport athletes (n = 205), all European Caucasians, we found no association between the ACTN3 R577X polymorphism and team-sport athletic status. We assume that the inconsistent results provided by some previous reports [12][13][14] can be attributed to the relatively small sample size of the studied cohorts, and consequently low statistical power. This supports the need for larger cohorts with clearly defined phenotypes to reach more solid conclusion in human association studies.…”
Section: Discussionmentioning
confidence: 83%
“…Santiago et al 11 showed higher proportions of the 577RR genotype in world-class professional soccer players (n = 60) compared with non-athletic controls and elite endurance athletes. In contrast, no association was found between the ACTN3 R577X polymorphism and athletic performance in a mixed group of elite Lithuanian athletes, 12 in Welsh rugby union players (n = 102), 13 or in Italian team-sport athletes (i.e., football, basketball, and hockey players; n = 65). 14 The inconsistent results in the aforementioned studies performed with elite team-sports athletes may be due to an insufficient sample size, associated with the low number of elite athletes available for analysis.…”
Section: Introductionmentioning
confidence: 81%
“…It should be noted that several studies have demonstrated no association between the ACE I/D polymorphism and endurance athlete status [28][29][30][31][32][33][34][35] or prevalence of the D allele (or low proportion of the II genotype) in endurance-oriented athletes in comparison with controls [19,[36][37][38]. Furthermore, Tobina et al [29] have shown that average running speed was significantly higher for those Japanese endurance runners with the combined DD/ID genotypes than for those with the II genotype.…”
Section: Ace I Allelementioning
confidence: 92%